PENGARUH MOTIVASI, PARENTAL INFLUENCE, DAN PENGETAHUAN ARTIFICIAL INTELLIGENCE TERHADAP MINAT MAHASISWA AKUNTANSI DALAM MEMILIH KARIER SEBAGAI AKUNTAN PUBLIK (STUDI KASUS: MAHASISWA AKUNTANSI PERGURUAN TINGGI DI KOTA BENGKALIS) - Santia, Eni; Rosmida, Rosmida (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, 2025)
This study aims to analyze the influence of motivation, parental influence, and knowledge of Artificial Intelligence (AI) on accounting students' interest in choosing a career as a public accountant at a college in Bengkalis Regency. The approach used is quantitative with data collection through questionnaires distributed to 132 7th semester accounting students from Bengkalis State Polytechnic, STIE, and STAIN using purposive sampling techniques. The results showed that motivation did not have a significant effect on student interest, with a t-count value of 1.389 which was smaller than the t-table of 1.657 and a significance of 0.167 (> 0.05). Parental influence has a positive and significant effect on student interest, with a t-count value of 8.098 (> t-table 1.657) and a significance of 0.000 (< 0.05). Knowledge of AI did not have a significant effect with a t-count value of 0.733 and a significance of 0.465 (> 0.05). Simultaneously, the three factors have a significant effect on student interest with an F-count value of 35.776 and a significance of 0.000 (<0.05). This finding provides insight to educators and policy makers to pay attention to the role of parental influence in students' career decisions. This study also provides new contributions in understanding the factors that influence students' interest in choosing a career as a public accountant.